Mueller Matrix Imaging Optimized by Uniform Illumination - Guo, Wei; Song, Jiawei; Zeng, Nan; Ma, Hui (Frontiers in Physics, 2022)
In this study, we present a flat-field Mueller matrix imaging system to reduce the reconstruction error caused by critical illumination. This study demonstrates that the signal-to-noise ratio (SNR) of the reconstructed images is improved by about eight times by adding a beam shaping module made up of microlens arrays to a traditional Mueller system. The scalar diffraction theory and polarization numerical simulation show the ability of the new device in minimizing the adverse effects of light source noise on polarization reconstruction results. Finally, the experiment results on standard resolution board, porous anodic alumina, and real pathological slices further confirm the superiority of the flat-field Mueller system in precisely identifying sample structure and quantitative differences between various polarization parameters (depolarization ratio Δ, linear retardance δ, and birefringence orientation θ), demonstrating the potential of flat-field polarization imaging in pathological diagnosis and tissue characteristic extraction.